Impurity effects on the Lattice Thermal Conductivity in the Ternary GuG2P3 Semiconductor - Omer, Mustafa Saeed (Sulaimani Journal for Pure and Applied Sciences, 2004)
The callaway model is used to calculate lattice thermal conductivity for the doped CuGe2Pr semiconductor between 1 and 300K. Generally, the effects of doping with S, Se, Zn, are increase this phenomena exoept for that af Ln-Zt:t doped which is reduces thermal conductivity from that of the undoped samples. The lughest values of r( is found for the 7-n-doped sample to be 0.57Wcm.K while the lowest is found far I*Zn doped to be 0.15 Wcm.K. The effects of the impurity concentrations N at K** is changes according to N0'622 and the r(,* for all concentrations does not affected by the temperature. Results are analysed according to; first, the Rayleih scattering process with the longe wave length effect as well as the resonance scattering process and, second is the dependence on the chemical formation of the compound. Key Words : lattice thermal conductivity, Semieonductors, CuGe2P3, Ternary compounds.